Highlights on the Management of Oligometastatic Disease - Salem M. Alshehri; Khaled Alkattan; Ahmed Abdelwarith; Hussain Alhussain; Shaker Shaker; Majed Alghamdi; Hossam Alassaf; Ali Albargawi; Manal Al Naimi; Ameen Alomair; Saif Althaqfi; Adnan Alhebshi; et al. (Journal of Immunotherapy and Precision Oncology, 2020)
Purpose: The understanding of oligometastatic disease (OMD) is rapidly evolving and with this comes the ability to utilize a number of modalities that excel in the localized control of disease. It has been identified that there are no clear guidelines based on high-level evidence to standardized approaches toward the management of OMD. These highlights have been developed to provide a road map for all health-care professionals who are involved in the management of OMD to support standardized patient care. Methods: The Saudi Lung Cancer Guidelines Committee is a part of the Saudi Lung Cancer Association which, in turn, is part of the Saudi Thoracic Society. Considering that lung cancer constitutes a major proportion of OMD prevalence, the committee took the initiative to develop national highlights to support the management of OMD within Saudi Arabia. The committee members are national clinical leaders who collaborated with international expertise to establish these highlights to serve as a general clinical pathway in the management of OMD. Results: Standardization of the indications to diagnose oligometastases and patient selection criteria including ineligibility criteria for treatment are the basis of the highlights. Treatment approaches including surgical and the variety of radiotherapeutical options are discussed in relation to specific oligometastatic sites. Acceptable measurements for response to treatment and the future for the treatment of OMD conclude the development of the highlights. Conclusion: These are the first national highlights addressing this important disease in oncology. The implementation of these highlights as guidelines requires a robust multidisciplinary team and access to specific technology and expertise. These highlights are based on the most recent findings within the literature but will require repeated review and updating due to this rapidly evolving field in disease management.